Hypocholesterolemic effect of dietary fibre powder from pink guava by-product - Ibrahim, Aida Hamimi; Hassan, H.; Ismail, A.; Samad, A. N.; Nordin, N. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
This study analysed the hypocholesterolemic effect of dietary fibre powder (DFP) from pink guava by-product in Male Sparague-Dawley rats. In studying the hypocholesterolemic effect of DFP, 3 groups of 8 rats each was used. The three groups in this study were normal rats (basal diet), control rats (basal diet + 1% cholesterol and 0.2% cholic acid), and treated rats (10% DFP + 1% cholesterol and 0.2% cholic acid). The experimental results showed that there was no significant difference (p>0.05) in the mean body weight gained and food efficiency between the rat’s feds with 10% DFP and those rats in control and cholesterol diet. As expected, 10% DFP had remarkable fecal bulking effect with fresh weights of feces were significantly (p<0.05) higher than in control and cholesterol group. Supplementation of 10% DFP had reduced total serum cholesterol (43%) and low-density lipoprotein levels (51%), however the high density and triglycerides levels were not affected within 30 days of experiments. From the lipid profiles analysis, it shown that DFP from pink guava by-product has potential to reduce total cholesterol, LDL-cholesterol and decrease the risk of cardiovascular diseases by decreasing the atherogenic index in rats. A potential cholesterol-lowering DFP could offer an opportunity to explore new product formulation utilizing pink guava processing by-product.